Entrepreneurial Value Proposition Proficiency Diagnosis: A KAP Model Dimension - Ishmael Obaeko IWARA (Management and Economics Review, 2024)
The persistently high attrition rates of small, medium, and micro enterprises in most economies globally hinges significantly on challenges stemming from lack of business dynamism and intense competition. This study explores the entrepreneurial proficiency of entrepreneurs in value proposition skills, a pivotal resource in mitigating homogeneity-related business failures. Using the KAP framework, variables within knowledge (awareness, comprehension and competence), attitudes (perception, intention and consistency) and practices (target audience, differential offerings, customer value) were scrutinised across cohorts (gender, location, and support status). Through a non-parametric analysis on a data structure obtained from conducting a 5-Likert type scale survey with 648 entrepreneurs, the findings explains that while awareness of the value proposition is notably high across respondents, supported entrepreneurs outshine their unsupported counterparts. Comprehension and competence, however, exhibit comparatively lower values, particularly among unsupported entrepreneurs, and despite a positive perception, the intention and consistency levels regarding the value proposition concept are sub-par across all groups. In terms of practice, factors such as target audience and differential offerings are below average, emphasizing the need for strategic and pragmatic interventions. The result indicates an overall deficiency in value proposition proficiency, stressing targeted soft and hard entrepreneurial skills interventions to foster not only value proposition acumen but market positioning, entrepreneurial resilience, and enterprises efficacy in the competitive business landscape.